Soil insects associated with lucumo (Pouteria lucuma L.) trees in La Molina, Lima, Peru - Livia, C. (2019)
This study aimed to determine the composition and relative abundance of soil insects associated with lucumo (Pouteria lucuma L.) trees growing in the agricultural fields of the Universidad Nacional Agraria La Molina in Lima, Peru. In total, 12 pitfall traps were installed in a 5-ha lucumo field and samples were collected on a weekly basis for approximately 4 months (March–June). Insects in each sample were separated into morphotypes, and the number of individuals in each morphotype and date of collection were recorded. The collected insects were then identified at the Entomology Museum laboratory in Lima through comparison with museum samples and with the help of identification keys. Individuals in the orders Orthoptera (families Acrididae and Gryllidae), Dermaptera (Anisolabididae), Coleoptera (Carabidae, Staphylinidae, Tenebrionidae, Scarabaeidae and Elateridae), Blattodea (Blatellidae) and Hymenoptera (Formicidae) were identified. Among the Coleoptera, Tetracha chilensis (Laporte, 1834) (Carabidae) was the most abundant species; furthermore, Staphylinidae of the subfamily Oxytelinae and the families Elateridae (Conoderus spp.), Tenebrionidae (Epitragopsis sp.) and Scarabaeidae (Ataenius sp.) were identified. Additional taxa identified were as follow: Gryllus assimilis (Fabricius, 1775) (Gryllidae) in Orthoptera, Euborellia annulipes (Lucas, 1847) (Anisolabididae) in Dermaptera and Linepithema spp. in Hymenoptera.